It’s Magic, You Know: The Reframing of Ozempic as a Weight Loss Drug - Herring, Matthew (The Motley Undergraduate Journal, 2024)
Advertising for Ozempic is inescapable. We have come to expect an advertisement for Ozempic around every corner. From scrolling social media to watching a hockey game, Ozempic is everywhere. This paper seeks to understand the multilayered and multimedia advertising campaigns, alongside lay-advertising on social media platforms that have allowed Ozempic and its producer Novo Nordisk to redefine and reframe the drug from its intended use as an insulin-producing type 2 diabetes medication to a widely sought-after weight loss medication. My analysis examines the role of social media in shaping consumer perceptions of Ozempic, the influence of direct-to-consumer advertising in promoting off-label uses, and the resulting consequences on drug accessibility and health perceptions. Specifically, by scrutinizing media portrayals on TikTok and direct-to-consumer advertising strategies, this paper unveils the dynamics of pharmaceutical product reframing and its effects on the dominant discourses surrounding said products. As Ozempic attempts to redefine what a healthy body should look like, it is imperative to analyze how social media and pharmaceutical advertising campaigns shift cultural understanding, reinforcing anti-fat narratives and limiting access to life-saving drugs for those who need them.